Accelerated infliximab infusions for inflammatory bowel disease improve effectiveness - McConnell, John (Baishideng Publishing Group Co., Limited, 2012)
AIM: To study the safety and effectiveness associated with accelerated infliximab infusion protocols in patients with inflammatory bowel disease (IBD). METHODS: Original protocols and infusion rates were developed for the administration of infliximab over 90-min and 60-min. Then the IBD patients on stable maintenance infliximab therapy were offered accelerated infusions. To be eligible for the study, patients needed a minimum of four prior infusions. An initial infusion of 90-min was given to each patient; those tolerating the accelerated infusion were transitioned to a 60-min infusion protocol at their next and all subsequent visits. Any patient having significant infusion reactions would be reverted to the standard 120-min protocol. A change in a patient’s dose mandated a single 120-min infusion before accelerated infusions could be administered again. RESULTS: The University of Virginia Medical Center's Institutional Review Board approved this study. Fifty IBD patients treated with infliximab 5 mg/kg, 7.5 mg/kg and 10 mg/kg were offered accelerated infusions. Forty-six patients consented to participate in the study. Nineteen (41.3%) were female, five (10.9%) were African American and nine (19.6%) had ulcerative colitis. The mean age was 42.6 years old. Patients under age 18 were excluded. Ten patients used immunosuppressive drugs concurrently out of which six were taking azathioprine, three were taking 6-mercaptopurine and one was taking methotrexate. One of the 46 study patients used corticosteroid therapy for his IBD. Seventeen of the patients used prophylactic medications prior to receiving infusions; six patients received corticosteroids as pre-medication. Four patients had a history of distant transfusion reactions to infliximab. These reactions included shortness of breath, chest tightness, flushing, pruritus and urticaria. These patients all took prophylactic medications before receiving infusions. 46 patients (27 males and 19 females) received a total of fifty 90-min infusions and ninety-three 60-min infusions. No infusion reactions were reported. There were no adverse events, including drug-related infections. None of the patients developed cancer of any type during the study timeframe. Total cost savings for administration of the both 90-min and 60-min accelerated infusions compared to standard 120-min infusions was estimated to be $53 632 ($116 965 vs $63 333, P = 0.001). One hundred and eighteen hours were saved in the administration of the accelerated infusions (17 160 min vs 10 080 min, P = 0.001). In the study population, overweight females [body mass index (BMI) > 25.00 kg/m(2)] were found to have statistically higher BMIs than overweight males (mean BMI 35.07 ± 2.66 kg/m(2) vs 30.08 ± 0.99 kg/m(2), P = 0.05), finding which is of significance since obesity was described as being one of the risk factors for Crohn’s disease. CONCLUSION: We are the first US group to report substantial cost savings, increased safety and patient satisfaction associated with accelerated infliximab infusion.